‘Horses for courses’ – an interrogation of tools for marine ecosystem-based management - Nadia Papadopoulou; Christopher John Smith; Anita Franco; Michael Elliott; Angel Borja; Jesper H. Andersen; Eva Amorim; Jon P. Atkins; Steve Barnard; Torsten Berg; Silvana N. R. Birchenough; Daryl Burdon; et al. (Frontiers in Marine Science, 2025)
Marine Ecosystem-Based Management (EBM) approaches are a well-established and fundamental component of international agreements and treaties, regional seas conventions, assessment strategies, European Directives and national and regional instruments. However, there is the need to interrogate and clarify the implementation of EBM approaches under current marine management. Although particular focus here is within the European Union Marine Strategy Framework Directive (MSFD), all lessons learned are applicable to marine assessments and management in seas worldwide given that all marine management instruments aim to ensure sustainability in marine ecosystems and human uses. Notably, the MSFD aims to ensure that Good Environmental Status (GES) will be achieved thereby enabling the sustainability of coastal and marine ecosystems to deliver ecosystem services and societal goods and benefits while at the same time being adaptive to rapid climate and environmental changes. As a clear understanding of EBM and the tools available to achieve it is needed for practitioners, regulators and their advisors, the analysis here firstly presents the current understanding of EBM (including its origin and application) and the wider 26 principles on which it is based. Secondly, we identify the key elements that are addressed by those principles (18 key EBM elements). Thirdly, we identify the types of tools available for use in the EBM context (19 tool groups). Fourthly we analyze the suitability of tool types to deliver the key EBM elements using an expert judgement approach. Finally, we conclude with the lessons learned from the use of those tools and briefly indicate how they could be combined to help achieve EBM in the most effective way. It is emphasized that no single tool is likely to satisfy all aspects of EBM and therefore employing a complementary suite of tools as part of a toolbox is recommended.

Innovative and practical tools for monitoring and assessing biodiversity status and impacts of multiple human pressures in marine systems - Angel Borja; Torsten Berg; Hege Gundersen; Anders Gjørwad Hagen; Kasper Hancke; Samuli Korpinen; Miguel C. Leal; Tiziana Luisetti; Iratxe Menchaca; Ciaran Murray; GerJan Piet; Sophie Pitois; et al. (Environmental Monitoring and Assessment, 2024)

What Is Marine Biodiversity? Towards Common Concepts and Their Implications for Assessing Biodiversity Status - Sabine K. J. Cochrane; Jesper H. Andersen; Torsten Berg; Hugues Blanchet; Angel Borja; Jacob Carstensen; Michael Elliott; Herman Hummel; Nathalie Niquil; Paul E. Renaud (Frontiers in Marine Science, 2016)

A Catalogue of Marine Biodiversity Indicators - Heliana Teixeira; Torsten Berg; Laura Uusitalo; Karin Fürhaupter; Anna-Stiina Heiskanen; Krysia Mazik; Christopher P. Lynam; Suzanna Neville; J. German Rodriguez; Nadia Papadopoulou; Snejana Moncheva; Tanya Churilova; et al. (Frontiers in Marine Science, 2016)

Biodiversity in Marine Ecosystems—European Developments toward Robust Assessments - Anna-Stiina Heiskanen; Torsten Berg; Laura Uusitalo; Heliana Teixeira; Annette Bruhn; Dorte Krause-Jensen; Christopher P. Lynam; Axel G. Rossberg; Samuli Korpinen; Maria C. Uyarra; Angel Borja (Frontiers in Marine Science, 2016)

Bridging the Gap between Policy and Science in Assessing the Health Status of Marine Ecosystems - Angel Borja; Michael Elliott; Paul V. R. Snelgrove; Melanie C. Austen; Torsten Berg; Sabine Cochrane; Jacob Carstensen; Roberto Danovaro; Simon Greenstreet; Anna-Stiina Heiskanen; Christopher P. Lynam; Marianna Mea; et al. (Frontiers in Marine Science, 2016)

Indicator-Based Assessment of Marine Biological Diversity–Lessons from 10 Case Studies across the European Seas - Laura Uusitalo; Hugues Blanchet; Jesper H. Andersen; Olivier Beauchard; Torsten Berg; Silvia Bianchelli; Annalucia Cantafaro; Jacob Carstensen; Laura Carugati; Sabine Cochrane; Roberto Danovaro; Anna-Stiina Heiskanen; et al. (Frontiers in Marine Science, 2016)

Overview of Integrative Assessment of Marine Systems: The Ecosystem Approach in Practice - Angel Borja; Michael Elliott; Jesper H. Andersen; Torsten Berg; Jacob Carstensen; Benjamin S. Halpern; Anna-Stiina Heiskanen; Samuli Korpinen; Julia S. Stewart Lowndes; Georg Martin; Naiara Rodriguez-Ezpeleta (Frontiers in Marine Science, 2016)

Tales from a thousand and one ways to integrate marine ecosystem components when assessing the environmental status - Angel Borja; Theo C. Prins; Nomiki Simboura; Jesper H. Andersen; Torsten Berg; Joao-Carlos Marques; Joao M. Neto; Nadia Papadopoulou; Johnny Reker; Heliana Teixeira; Laura Uusitalo (Frontiers in Marine Science, 2014)

Current status of macroinvertebrate methods used for assessing the quality of European marine waters: implementing the Water Framework Directive - Angel Borja; Alison Miles; Anna Occhipinti-Ambrogi; Torsten Berg (Hydrobiologia, 2009)